SISTEM INFORMASI KRS ONLINE TERINTEGRASI PDDIKTI PADA JURUSAN TEKNIK INFORMATIKA UPR (Universitas Palangka Raya, 2017)
AbstractKRS is a system for determining a course to be taken by students in one semester.Department of Information Engineering at University of Palangkaraya (UPR) still uses a manualform that consuming much time for lecturer and students. Lecturer have to check studentachievement index as know as IP (Indeks Prestasi), to determine the number of credits taken bystudents. Web-based information system have to develop to assist the process of preparing the KRS.Higher Education Data Base (PDDIKTI/Pangkalan Data Pendidikan Tinggi) is a collection of dataderived from the entire College of Higher Education that is integrated nationally. The process ofupdating the data on pddkti conducted by each university. Therefore, KRS system developmentshould be integrated with the database PDDIKTI. System Update on PDDIKTI using web servicemethods that have been provided by PDDKTI through the feeder-DIKTI applications.